If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-1)+4(x+2)=18
We simplify the equation to the form, which is simple to understand
2(x-1)+4(x+2)=18
Reorder the terms in parentheses
+(+2x-2)+4*(x+2)=18
Remove unnecessary parentheses
+2x-2+4+*(+x+2+)=+18
Reorder the terms in parentheses
+2x-2+(+4x+8)=18
Remove unnecessary parentheses
+2x-2+4x+8=+18
We move all terms containing x to the left and all other terms to the right.
+2x+4x=+18+2-8
We simplify left and right side of the equation.
+6x=+12
We divide both sides of the equation by 6 to get x.
x=2
| -2(t-5)+9t=5t-6 | | -3(x-1)-10=12+8 | | 1/5(x/2+3/4)=1/4 | | (x+8)x= | | -6w+16=-9 | | x/2+7x=180 | | 5.8(x-4)=-0.2x+12.8 | | -7x+5=5x-7 | | 7x-48=12+2x | | 0=x^3-x^2 | | 2(3.5*-3.111+6)=2.5*-3.111-2 | | 40x+15=5(5x-18) | | -12(4-3x)=-x+3(12x-9) | | 3x-5(x-4)=-3+2x+7 | | -4(2x+1)=-5-3x | | 15-4k=12-7x | | 4x^3-40x^2+84x= | | 2b+4=-18-(-9b) | | 2(x+1)=6(x-3) | | 12(4-3x)=-x+3(12x-9) | | 2a+3b-2c=18 | | 2a+3b-2c=17 | | 0=3x+2x^2-x^3 | | -2(5y-1)+4y=-4 | | 36=-2(4y+2) | | 18=3(w-2) | | -4(p+2)+8=2(p-1)7p+15 | | ln(x+3)+ln(x-3)=4 | | 3x+5y+2x+3x+5x+7-4= | | -4x+-12x-39=137 | | 1.3(x+3)+2.3x=6 | | 6p-1=3p+8 |